Notes on the nomenclature of the New Zealand endemic Triozidae (Hemiptera: Sternorrhyncha: Psylloidea). Issue 1 (2nd January 2021) - Martoni, Francesco; Nelson, Warrick; Brown, Samuel D. J.
ABSTRACT: The New Zealand psyllid fauna is characterised by a large number of endemic Triozidae. These species have been subject to changes in generic placement through their taxonomic history. Powellia Maskell, 1879, has been considered by various authors as either a valid genus, or as a synonym of the cosmopolitan genus Trioza Foerster, 1848, including by Maskell himself. In this note, we review the taxonomic history of the species within this taxon, and discuss the morphological, genetic and ecological evidence for the recognition of Powellia Maskell, 1879, as a valid genus. Consequently, we establish the following New combinations : P. alseuosmiae (Tuthill, 1952 ), P. australis (Tuthill, 1952 ), P. compressa (Tuthill, 1952 ), P. crinita (Tuthill, 1952 ), P. dacrydii (Tuthill, 1952 ), P. dentiforceps (Dumbleton, 1967 ), P. discariae (Tuthill, 1952 ), P. flavida (Tuthill, 1952 ), P. gourlayi (Tuthill, 1952 ), P. hebicola (Tuthill, 1952 ), P. latiforceps (Tuthill, 1952 ), P. obscura (Tuthill, 1952 ), P. parvipennis (Tuthill, 1952 ), P. schefflericola (Tuthill, 1952 ), P. scobina (Tuthill, 1952 ), P. subvexa (Tuthill, 1952 ), all from Trioza . A further two species, T. adventicia Tuthill, 1952 and T. curta (Ferris & Klyver, 1932 ) are retained in Trioza .